Hasil Belajar Matematika Siswa Sekolah Dasar: Tingkatan Kelas dan Gender - Siregar, Nurdiana; Hoiriyah, Diyah; Sapitri, Liya (IAIN PADANGSIDIMPUAN, 2020)
This study aims to examine student mathematics learning outcomes in terms of each grade level in elementary school and gender. This study uses a descriptive design conducted at SD Negeri 104245 Tumpatan. Data obtained by looking at the value of student mathematics learning outcomes (documents), the subject of which a total of 300 people (163 male and 138 female). Data were analyzed with descriptive analysis techniques using the normal curve approach. The results showed that the average mathematics learning outcomes of class I students for male students were 72 with low categories and women scored 73 with medium categories, class II students for men rated 71 with low categories and female grades 76 with medium categories, students class III 70 with low categories for men and women, class IV students with a score of 82 with a moderate category both male and female students, class V with a grade of 82 with a moderate category obtained by men and women, and class VI students for males, 80 were obtained in the medium category and women scored 83 in the medium category.